The relationship between self-cohesion and smartphone addiction: the mediating role of rejection sensitivity - El Keshky, Mogeda El Sayed; Aseem, Huda; Alzain, Amira; Samak, Yasser Abdelazim Abdelmawgoud (Frontiers in Public Health, 2023)
The increasing use of smartphones with attractive applications has yielded a concern about problematic overuse, also called smartphone addiction, thus creating a need to investigate the antecedents and pathways of this addiction. The aim of this study was to investigate the relationship between self-cohesion dimensions, presence and consistency and smartphone addiction, and the potentially mediating role of rejection sensitivity. A total sample of 910 respondents (58% females, mean age = 34.9, SD = 13.6) participated in the study. They completed a questionnaire containing demographic questions as well as the Self-Cohesion Scale, the Short Version of Smartphone Addiction Scale, and the Rejection Sensitivity RS-Adult Questionnaire. Structural equation modeling was used to examine the relationships in question. The findings indicated that smartphone addiction negatively positively correlated with rejection sensitivity, and negatively correlated with presence and consistency. Further, self-cohesion dimensions, presence and consistency were negatively associated with smartphone addiction, and rejection sensitivity negatively mediated these relationships. Efforts to counteract smartphone addiction should endeavor to increase smartphone users’ self-cohesion and reduce their rejection sensitivity.